UNDERSTANDING “GEOPOLITICS” IN AN ERA OF GLOBALIZATION - Agnew, John (Revista Tamoios, 2016)
An older European-Enlightenment geopolitical imagination was lost in the late nineteenth century with the rise of naturalized understandings of inter-state and imperial relations that saw states and empires in terms of biological competition conditioned by relative location on the earth’s surface. The word “geopolitics” emerged in that context and since that time the term has had to contend with this original sin. Arguably, however, Montesquieu and Voltaire in their references to Alexander the Great had a somewhat different conception of geopolitics in mind: one in which reciprocity and exchange between places as well as the redistribution of resources from colonies to homeland are at work. It is this broader sense of the word that has been revived over the past fifty years in the course of attempts at linking the global political structure of states, empires, and other political authorities to what can be called the “globalization era.” The broader understanding of geopolitics is by no means restricted to this era, as the reference to the Enlightenment period should make clear. But it has become an increasingly attractive alternative. I discuss four aspects of the connection between geopolitics construed in the broader meaning and the globalization that the world economy has experienced over the past fifty years. The first is to challenge the idea that geopolitics in the broad sense is “opposed” to globalization. I then turn to what I see are the three dimensions of geopolitics in an era of globalization: the geopolitics of globalization, the geopolitics of development, and the geopolitics of global regulation. From this perspective, Montesquieu and Voltaire offer a much better inspiration for understanding world politics than do the geopolitical writers of the early twentieth century such as Kjellen and Mackinder.